PARAMETER PENENTU PENGGUNAAN TRANSPORTASI UMUM DI PERKOTAAN PATI - Bekti Winarno; Okto Risdianto Manullang (Diponegoro University, 2018)
The research aims to analyze and assess determining parameters for public transportation usage for choice user group among the labours that work in Pati Urban Area; therefor the most dominant parameters will be known. User satisfaction recently used in public transportation researches and widely believed as determinant of mode choice. This research is using Structural Equation Modelling (SEM) Analysis with 150 sampels of Pati Urban Area labours (including public servant and private workers) choosen by purposive sampling technique. The findings of the reasearh are : connectivity, accessibility and service quality have positive and significant impact toward user disatisfaction and user disatisfaction influences traveller behaviour to unuse public transportation services, while influence of travel cost couldn’t be explained and estimated. Finally, answering the research question, research reveals that connectivity’s parameters (0,563 influence rate), i.e waiting time, desireable arrival schedule and travel time, are the most dominant to determine public transportation usage with accessibility’s parameters (0,462) at the next ranking. At the lower rangking but also significant are service quality’s parameters with 0,451 influence rate.